DESAIN ULANG INSTALASI PERPIPAAN PADA MESJID NOOR BANJARMASIN - Muhammad Firman; Muhammad Irfansyah; Budi Hartadi; Heri Irawan; Mujiburrahman Mujiburrahman (Universitas Islam kalimantan MAB, 2017)
Service aims to assist the pilgrims so that not too long queue when the purification ritual, so that problems that had been faced by the mosque Noor about the uneven distribution of water during ablution can be resolved by means of installing a piping system so that the water supply everyone on water tank or reservoir can be filled and evenly all these divisions reservoir, so that when the full-full of pilgrims could be served all and not so many pilgrims who cannot attend the prayer in congregation. The main target of this activity is the management of the mosque and the mosque, because they always get complaints and direct censure of pilgrims due to uneven supply of water during ablution, so they need to know how to properly install piping system.The method used to achieve the objectives that have been implemented are: to perform the installation of the channel that goes into reservoirs and channels out of the reservoir so that the distribution of water for ablution can be evenly and flowed perfectly.From the results of this activity all the reservoir can get a direct supply from the pump or other sources, the supply of water for ablution can run smoothly is that during these 14 taps of 43 taps for ablution place of men who do not get water supply now is 100% get water or completely get water supply, in the place of ablution women there are six taps that do not get water from 17 taps installed there now entirely get water supply, as well as the bathroom which amounted to 14 taps, as well as urinal male 8 taps obtain equitable water supply. Djuhur prayers and implementation are now only approximately 1 shap or 40 worshipers who pray it too late due to the late arrival of pilgrims.